The Effect of Dryness on the Prevalence of Few Cases of Cutaneous Leishmaniasis in North Iraq - Salman, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This is a contribution to study the complex effect of rainfall on the incidence of cutaneous leishmaniasis in an endemic area (AL-Mohalabiya) in Ninava province in the north region of Iraq.